2022
DOI: 10.1038/s41586-022-05147-5
|View full text |Cite|
|
Sign up to set email alerts
|

Layered subsurface in Utopia Basin of Mars revealed by Zhurong rover radar

Abstract: Exploring the subsurface structure and stratification of Mars advances our understanding of Martian geology, hydrological evolution and palaeoclimatic changes, and has been a main task for past and continuing Mars exploration missions1–10. Utopia Planitia, the smooth plains of volcanic and sedimentary strata that infilled the Utopia impact crater, has been a prime target for such exploration as it is inferred to have hosted an ancient ocean on Mars11–13. However, 45 years have passed since Viking-2 provided gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 78 publications
(52 citation statements)
references
References 62 publications
(113 reference statements)
2
50
0
Order By: Relevance
“…As the structure of the Martian subsurface is more clearly detected by radar in Zhurong area (Li et al, 2022), more refined thermodynamic models based on the detected structure would provide more accurate results for the temperature analysis of the subsurface in this region. For example, the modeling of both the martian regolith and the filled rocks using the finite-element method can accurately simulate the temperature distribution and its variation for the martian subsurface.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…As the structure of the Martian subsurface is more clearly detected by radar in Zhurong area (Li et al, 2022), more refined thermodynamic models based on the detected structure would provide more accurate results for the temperature analysis of the subsurface in this region. For example, the modeling of both the martian regolith and the filled rocks using the finite-element method can accurately simulate the temperature distribution and its variation for the martian subsurface.…”
Section: Discussionmentioning
confidence: 99%
“…It would be very helpful to analyze the underground structure and thermal state (temperature field) based on three-dimensional simulations. Although the previous study has revealed the structure of the subsurface under the Zhurong landing site (Li et al, 2022). However, the detailed threedimensional structure of the shallowest 10 m remains enigmatic.…”
Section: Heat Conduction Equationmentioning
confidence: 96%
See 3 more Smart Citations